Reinventing refills: guidelines for design. Issue 12 (9th August 2017) - Lofthouse, Vicky; Trimingham, Rhoda; Bhamra, Tracy
Abstract : This paper draws on the findings of a Department for Environment and Rural Affairs funded collaborative research project run by the Loughborough Design School in collaboration with Boots Alliance GmbH and presents guidelines for design teams regarding the design of successful, sustainable, refillable packaging. The study focused on "body wash" products in the area of personal care. A broad range of qualitative methods were used to create a background framework, develop design concepts, and test the viability of the design solutions. Two concepts were turned into high‐fidelity prototypes and tested in multi‐activity user focus groups. The prototypes were also evaluated from an environmental perspective using the Eco Indicator 99. Discussion is focused around general findings regarding refillable packing and also on specific findings related to "concentrates mixed in the parent pack." The findings from this study have dramatically increased levels of understanding about the potential implications of refillable packaging and how it might be successfully used by business. A range of guidelines for the design of refills have been identified, which help to build a clearer picture of the requirements of successful refillable packaging design. Additionally, a much more detailed understanding of consumer perceptions, business challenges/opportunities, and environmental savings associated with "concentrated refills that are mixed in the parent pack, " has been identified. It has been seen that to be successful refills must perform for the consumer, the environment, and business, and although this may sound unsurprising, it is challenging to achieve. It means they must offer good quality; be very easy to use and appropriately delivered; be clearly communicated; be offered through a brand consumers like; and represent good value, whilst radically reducing the amount of packaging manufactured and distributed. Incorporating carefully considered consumer and environmental needs into the brief is critical to the successful development of refillable packaging. Abstract : This paper presents guidelines for design teams for the design of sustainable, refillable packaging. Refills must perform for the consumer, the environment, and business. They must offer good quality; be very easy to use and appropriately delivered; be clearly communicated; be offered through a brand consumers like; and represent good value, whilst radically reducing the amount of packaging manufactured and distributed. Incorporating carefully considered consumer and environmental needs into the brief is critical to the successful development of refillable packaging.